PEDOT:PSS wrapped NiFe2O4/rGO tertiary nanocomposite for the super-capacitor applications. (20th May 2016) - Hareesh, K.; Shateesh, B.; Joshi, R.P.; Dahiwale, S.S.; Bhoraskar, V.N.; Haram, S.K.; Dhole, S.D.
Highlights: GNP has been synthesized in one-step for super-capacitor application. The Specific capacitance of GNP is found to be 1090 Fg −1 at 0.5 Ag −1 . PEDOT:PSS may provides active sites and also acts as a supporting layer for NiFe2 O4 . Abstract: A tertiary nanocomposite, PEDOT:PSS/NiFe2 O4 /reduced graphene oxide (rGO) (GNP) has been synthesized in one-step for super-capacitor application and its electrochemical performance has been compared with NiFe2 O4 /rGO, NiFe2 O4 /CNT/rGO and NiFe2 O4 /CNT. The specific capacitance of GNP nanocomposite is found to be 1090 Fg −1 and energy density of 660 Whkg −1 at a current density of 0.5 Ag −1 with cyclic stability of 94% of capacitance retention which are excellent values in its class. The well designed nanostructure and the synergetic effects of individual component results in enhanced electrochemical performance of GNP nanocomposite.